THE ANALYSIS OF THEME IN TEACHERS' QUESTIONS IN TEACHING HORTATORY EXPOSITION TEXT: A CASE OF EXPERIENCED AND NOVICE TEACHERS - Ni'mal Fuyudloturrohmaniyyah, - (2018)
Teachers' question is one of teaching strategies that facilitate students' understanding of the lesson. How the teacher's question is worded and structured is revealed in this qualitative case study through the use of Theme system analysis of SFL. The participants of this study are two English teachers, an experienced and a novice teacher. The analysis shows that the teachers' questions consist of Topical, Interpersonal and Textual themes along with Reiteration, Zigzag, Multiple, and Derived theme progressions. The most dominant Theme was Topical which appears to follow the genre being taught. The Topical themes were realized mostly in words What, Why, and How. These themes seem to lead the students to think about the hortatory exposition text, especially the questions and the issues raised in the text. Meanwhile, Reiteration is the most frequent Thematic Progression pattern realized in the teachers' questions. The high frequency of reiteration pattern takes place because the teachers tend to repeat the same questions to have the students' answers. In addition, the experienced and novice teachers' participants did not show significant differences in the quality of the questions. This study suggests that preparing teachers with pedagogically sound and critical questioning techniques could help develop the teachers' ability in teaching.